Linguistic Analysis of Knowledge Issues in Psychological Discourse (Journal of Science-Innovative Research in Uzbekistan, 2023)
This scientific article aims to explore the linguistic analysis of knowledge issues in psychological discourse. It highlights the importance of language in shaping and communicating psychological knowledge and examines theways in which language can both facilitate and hinder the understanding and dissemination of psychological concepts. Through a critical analysis of key psychological texts, this article identifies several linguistic issues that are prevalent in psychological discourse, including the use of technical jargon, the construction of binary oppositions, and the reliance on metaphorical language. The article concludes by suggesting that a more nuanced and reflexive approach to language is needed in psychological discourse to better capture the complexity of human experience